Polymorphism of gemfibrozil: Investigation by thermal and spectroscopic methods - Holanda, Bruno B.C. [UNESP]; Bannach, Gilbert [UNESP]; Ramos Silva, M.; Eusébio, M. Ermelinda S.; Castro, Ricardo A.E. (Elsevier, 2019)
The knowledge of polymorphism of active pharmaceutical ingredient is relevant in the pharmaceutical field. In this work, a multidisciplinary approach involving differential scanning calorimetry, polarized light thermal microscopy, X-ray powder diffraction and attenuated total reflectance infrared spectroscopy was used to investigate polymorphism of gemfibrozil (GEM), an important fibric acid derivative, in melting cooling/heating cycles. An amorphous phase, Tg = −34 °C, and two monotropic crystalline polymorphs with very close melting temperatures, form I, T fus,I = 59.0 °C, and form II, T fus,II = 58.0 °C, were identified, being form I the stable phase. In some experiments the forms were obtained concomitantly. The crystallization process seems to be dependent on molten liquid memory. Thereby, this effect could be due to low molecular mobility in the liquid state resulting from the relatively long carbon chain structure of GEM.
Keywords: Gemfibrozil; Memory effect; Polymorphism; Thermal analysis